Co-LivEn : COllective LIVing ENergy Dataset - Ramana R. Avula; Tobias J. Oechtering; Daniel Månsson (Royal Institute of Technology, 2022)
The dataset contains detailed electricity measurements of appliances in a collective living  (co-living) student apartment at KTH Live-in-Lab. The measurements included are RMS voltage, RMS current, real power, and power factor. The data was collected over a period of 277 days between 28th August 2020 and 31st May 2021 with 1 second time resolution. The compressed file "appliance_csv.zip" contains data in plain CSV file format, whereas "appliance_mat.zip" contains data in MATLAB file format.

For more detailed information and insights into the dataset and the data collection process, refer to the following article. Kindly cite this when using the dataset.

R. R. Avula, T. J. Oechtering and D. Månsson, "Adversarial Inference Control in Cyber-Physical Systems: A Bayesian Approach With Application to Smart Meters," in IEEE Access, vol. 12, pp. 24933-24948, 2024, doi: 10.1109/ACCESS.2024.3365270.
Keywords: appliance energy; smart meter; household energy; Energy Engineering; Energiteknik